2021
DOI: 10.3390/ma14247847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Mechanical and Corrosion Properties of Mg–Zn–Ga Biodegradable Mg Alloys

Abstract: Mg alloys have mechanical properties similar to those of human bones, and have been studied extensively because of their potential use in biodegradable medical implants. In this study, the influence of different heat treatment regimens on the microstructure and mechanical and corrosion properties of biodegradable Mg–Zn–Ga alloys was investigated, because Ga is effective in the treatment of disorders associated with accelerated bone loss. Solid–solution heat treatment (SSHT) enhanced the mechanical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In previous work, it was shown that the solution heat treatment of the Mg–Zn–Ga–(Y) alloys induced a high El (up to 15.2%) and produced a low fraction of intermetallic phases that provided high corrosion resistance [ 36 ]. However, aging had a low effect on the alloy strength and still has a low value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, it was shown that the solution heat treatment of the Mg–Zn–Ga–(Y) alloys induced a high El (up to 15.2%) and produced a low fraction of intermetallic phases that provided high corrosion resistance [ 36 ]. However, aging had a low effect on the alloy strength and still has a low value.…”
Section: Resultsmentioning
confidence: 99%
“…For melt protection from ignition, an Ar + 2 vol.% SF 6 protective atmosphere was used. The details of the melting procedure can be found elsewhere [ 36 ]. Cylindrical ingots with a diameter of 60 mm and a length of 200 mm were cast into an aluminum permanent mold preheated to 150 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some elements, such as beryllium and nickel, should be strictly controlled and even avoided as they may potentially cause adverse effects on the human body [ 24 ]. Heat treatment strategies and their influence on the corrosion properties of Mg–Zn–Ga alloys have been studied to investigate their usefulness for osteosynthesis applications, with promising results, such as a low corrosion rate and good mechanical properties [ 25 ]. Other techniques, such as surface modification and coatings with ceramic, polymeric, and hybrid materials, are effective in controlling the degradation rate of Mg [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mg alloys can obtain considerable mechanical properties upon Zn and Ga additions after deformation processing [ 17 , 18 , 19 ]. Ga’s effectiveness in treating disorders associated with accelerated bone loss, and its antibacterial properties, underline the potential of Ga as an alloying element for biodegradable Mg alloys [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%